2016
DOI: 10.5009/gnl14457
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Findings of Enteropathy-Associated T-Cell Lymphoma Type II: A Case Series

Abstract: Enteropathy-associated T-cell lymphoma (EATL) is a rare extranodal T-cell lymphoma arising from the intestine. Two types of EATL have been reported. In contrast to the classic EATL type I, EATL type II occurs sporadically, is unrelated to celiac disease, and comprises 10% to 20 % of all EATL cases. A total of five cases of EATL type II were diagnosed at our clinic from January 2009 to September 2012. Four of the five patients were diagnosed with the help of endoscopy. Among the four patients, two of the cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 10 publications
(9 reference statements)
0
27
1
Order By: Relevance
“…The endoscopic findings in 12 of the 15 reported cases of MEITL included circumferential ulcerated tumors and an edematous and granular mucosa, with a nodular or mosaic pattern, in the duodenum, jejunum, and ileum (Table 3 ) [ 15 24 ]. In addition, in all four patients, the non-neoplastic lesions consisted of an edematous or granular mucosa, with or without villous atrophy, in the duodenum and intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endoscopic findings in 12 of the 15 reported cases of MEITL included circumferential ulcerated tumors and an edematous and granular mucosa, with a nodular or mosaic pattern, in the duodenum, jejunum, and ileum (Table 3 ) [ 15 24 ]. In addition, in all four patients, the non-neoplastic lesions consisted of an edematous or granular mucosa, with or without villous atrophy, in the duodenum and intestine.…”
Section: Discussionmentioning
confidence: 99%
“…While of uncertain etiology, both lymphocytic and collagenous microscopic colitis are occasionally seen in patients with coeliac disease, hypothyroidism, diabetes mellitus, and rheumatoid arthritis [ 26 ]. In three reported cases of colonic MEITL, ulcerated tumors and hyperemic as well as normal-looking mucosa outside the tumors were detected (cases 2, 11, and 12 in Table 3 ) [ 15 , 23 , 24 ]. However, only the patient described by Kim et al had colonic MEITL characterized by presumably normal mucosa with tumor cell invasion [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a report of four cases, innumerable fine mucosal granules and diffuse thickening of the mucosa with semicircular shallow ulcerations were described in the small bowel and nonspecific changes in colon. 6 The endoscopic appearance in our first case differed from the above, with scattered shallow ulcerations with superficial exudates throughout the colon, within a background of rough mucosa with loss of vascular pattern. This pattern likely caused the initial consideration of UC.…”
Section: Discussionmentioning
confidence: 54%
“…It was reported that lymphoma cells in 21 of 31MEITL (68%) as well as 31 of 56 GI ATLL patients (55%) showed expression of CD103 homing receptor of T-IELs, and ATLL had similar histopathological characteristics to MEITL with respect to increased atypical and reactive T-IELs [18]. The endoscopic ndings of MEITL have been reported as edematous mucosa with mosaic and diffuse mucosal thickening patterns, and shallow ulceration, as well as ulcerative type tumors in the small intestine [21]. The endoscopic ndings of GI-involved acute type ATLL showed super cial spreading-type lesions (equal to the diffuse in ltrating type) in 12 of 23 lesions (52%) [22].…”
Section: Discussionmentioning
confidence: 97%